(untitled) (International Journal of Physiotherapy, 2014)
Background: Mulligan’s mobilization and Kinesio taping treatment techniques found to be effective on improving pain and functional disability for osteoarthritis of knee. Hence the purpose is to compare the effect of Mulligan’s mobilization and kinesio taping on improvement of pain and functional disability in subjects with osteoarthritis of knee. Method: An experimental study design, 40 subjects with osteoarthritis of knee joint randomized 20 subjects each into Mobilization Group and Taping Group. Mobilization Group was treated with Mulligan’s Mobilization and Taping Group was treated with Therapeutic Kinesio Taping thrice a week for 2 weeks. Outcome measurements such as Visual analog scale (VAS) for pain, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) for functional disability was measured before and after 2 weeks post intervention. Results: Analysis using Paired ‘t’ test and Wilcoxon signed rank test found that there is a statistically significant improvement in VAS and WOMAC within the group. Comparative analysis using Independent‘t’ test and Mann Whitney U test found there is a statistically significant difference in post-intervention means between the groups. Conclusion: The study concluded that both Mulligan’s Mobilization and Kinesio Taping techniques significantly shown short term effect on improvement of pain and functional disability for subjects with osteoarthritis of knee. However, there is no statistically significant difference in short term improvements between Mulligan’s Mobilization and Kinesio Taping. Among both, Mulligan’s Mobilization technique found clinically more effective with greater percentage of improvement than Kinesio Taping technique.